Implementasi Aplikasi Kasir dan Barcode Scanner untuk Pencatatan Keuangan dan Persediaan - Valenty, Yola Andesta; Anan, Edy (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity was motivated by the manual recording of transactions and inventory at the Koperasi Pemasaran Singosaren Maju Bersama, which lacked a cashier system and barcode scanner. The purpose of this activity is to improve the efficiency and accuracy of financial recording and inventory management through the implementation of a cashier application and barcode scanner, along with staff training. The method includes installing the cashier application, setting up the barcode scanner, and conducting technical training for the staff. The results show significant improvements in computerized recording and staff understanding. This simple yet appropriate technology proved effective in enhancing cooperative operations and can serve as replicable models for other cooperatives.